Aquatic forest food plants: scientific prospection on neglected nutritional potencial (Research, Society and Development, 2021)
Wild food plants offer possibilities for nutritional and economic diversification. They are considered as harmful species and grow spontaneously in gardens, vacant lots, among other environments including aquatic ones. Aquatic plants can also be inserted as a food resource with rich potential. Scientific research was carried out during the month of October 2020, based on the search for scientific articles dealing with the use of aquatic food plants and their nutritional composition in the Web of Science, Science direct and Pubmed databases. Additionally, searches were carried out in the book Non-Conventional Food Plants (PANC) on aquatic food plants occurring and used in Brazil. A total of 81 articles were computed for the keywords and respective combinations entered in the search field. After a more in-depth analysis of articles of interest, none of them presented content on wild and aquatic food plants and their nutritional composition. However, research has been identified that deals with terrestrial and aquatic plants used in food and the relationship established between man and the environment in vulnerable conditions. The expansion of the identification and use of food species, as well as the nutritional values added to research, allow the insertion of plants in sustainable diets. The scarcity of studies in this area allows the visualization of gaps in knowledge and ample possibilities for promising research in knowledge about biodiversity.